Spectroscopic and Spectrometric Approaches for Assessing the Composition of Embedded Metals in Tissues. Issue 6 (June 2021) - Smith, Diane E.; Todorov, Todor; Defante, Adrian P.; Hoffman, Jessica F.; Kalinich, John F.; Centeno, José A.
Many medical devices contain metals that interface with the body. Additionally, embedded metal fragments from military wounds are typically not removed, to avoid the risk of morbidity associated with invasive surgery. The long-term health consequences of many of these materials are not thoroughly understood. To this end, we have exposed rats for up to one year to implanted single-element metal pellets of any one of Al, Co, Cu, Fe, Ni, Pb, Ta, or W. Various tissues were harvested and flash frozen for analysis of their metal distribution. We discuss approaches to most thoroughly and reliably evaluate the distribution of metal in these tissues. The path to the most appropriate analytical technique took us through extensive examination of the tissues using scanning electron microscopy with energy dispersive X-ray spectroscopy (XPS), X-ray photoelectron spectroscopy (XPS), and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). Though any one of these methods is highly relied upon in surface chemistry analysis, LA-ICP-MS alone showed presence of metal in the tissue. This information will help build robust methods to bridge the gap in our understanding of biosolubility and distribution of embedded metal throughout the body.